Assembly-setup verification and quality control using machine vision within a reconfigurable assembly system - Bihi, Thabo George ([Bloemfontein?] : Central University of Technology, Free State)
The project is aimed at exploring the application of Machine Vision in a Reconfigurable Manufacturing System (RMS) Environment. The Machine Vision System interfaces with the RMS to verify the reconfiguration and positioning of devices within the assembly system, and inspects the product for defects that infringe on the quality of that product. The vision system interfaces to the Multi-agent System (MAS), which is in charge of scheduling and allocating resources of the RMS, in order to communicate and exchange data regarding the quality of the product. The vision system is comprised of a Compact Vision System (CVS) device with fire-wire cameras to aid in the image acquisition, inspection and verification process. Various hardware and software manufacturers offer a platform to implement this with a multiple array of vision equipment and software packages. The most appropriate devices and software platform were identified for the implementation of the project. An investigation into illumination was also undertaken in order to determine whether external lighting sources would be required at the point of inspection. Integration into the assembly system involved the establishment communication between the vision system and assembly system controller.
Thesis (M. Tech. (Engineering: Electrical)) -- Central University of technology, Free State, [2014]
Keywords: Central University of Technology, Free State - Dissertations; Computer vision; Multiagent systems; Assembly-line methods - Quality control; Adaptive computing systems - Quality control; Dissertations, Academic - South Africa - Bloemfontein